MANAJEMEN KEUANGAN RUMAH TANGGA TAKMIR MASJID RUNGKUT JAYA - Mas’amah Mas’amah; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The goal of this research is to understand how management financial implementation work into muslim Family, especially at Takmir Rungkut Jaya Mosque. The research used descriptive qualitative approach. Data collection was results by interview and documentation. Pattern matching technique was used to perform data analytic. This technique to find the general description of financial management family work into muslim then adjusted to the implementation of sakinah finance. The result based on interviews with two households of Takmir Rungkut Jaya Mosque is both informants in research has implemented components financial management to reach sakinah finance in the life daily. The financial management component are income management main intention to worship, meet family needs, maintain self-respect for not begging, and leniency of life, and hold the principle of halal in seeking sustenance and work, and focusing on the intention of the afterlife. Expenditure Management consists of three expenditure items, household needs posts, social posts, and mosque needs posts, as well as using savings as outposts for cash inflows and expenditures, as well as household emergency funds.Keyword: sakinah finance, income management, expenditure management, household financeREFFERENCESAl-Qur’an. Terjemahannya (Revisi Terbaru) Departemen Agama RI dengan transliterasi Arab-Latin. 2001. Semarang. CV. Asy Syifa.Abdulloh, Adil Fathi. 2007. Sudah Islamikah Kelaurga Anda? Pilar-Pilar Mewjudkan Keluarga Bahagia. Solo: Wacana Ilmiah Press.Antonio, Muhammad syafi’i. 2001. Bank Syariah dari Teori ke Praktek. Jakarta: Gema Insani Press.Antonio, Muhammad Syafi’i. 2011. Ensiklopedia Leadership dan Manajemen Muhammad SAW “The Super Leader Super Manager” Bisnis dan Kewirausahaan. Jakarta: Tazkia Publishing.Arnesih. 2016. Strategi Manajemen Keuangan Dalam Rumah Tangga (Berbasis Ekonomi Syariah). FKIP-UNRIKA. Vol 10 Februari 2016.Dispendukcapil Surabaya. 2016. Data Jumlah Perceraian di Surabaya. Surabaya: Dinas Kependudukan dan Pencatatan Sipil Surabaya. (http://Dispendukcapil.Surabaya.go.id diakses pada 16 Juni 2017).Manullang. 1981. Pengantar Ekonomi Perusahaan. Yogyakarta: Liberty.Quthb, Sayyid. 2004. Tafsir Fi Zhilalil di bawah nauangan Al-Qur’an Jilid 5. Jakarta: Gema Insani Press.Senduk, Safir. 2000. Seri Perencanaan Keuangan Keluarga Mengelola Keuangan Keluarga. Jakarta: PT. elex Media Komputindo.Sistem Informasi Masjid. 2017. Data jumlah masjid dan mushallah di Surabaya. Jakarta: Kementerian Agama Republik Indonesia. (http://simas.kemenag.go.id diakses pada 28 Maret 2017).Sugiyono. 2008. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta.Sulastiningsih. 2008. Cerdas Mengelola Keuangan Keluarga. Yogyakarta: Pro-U Media.Syaparuddin. 2014. Pengelolaan Keuangan Keluarga Secara Profesional dalam Mewujudkan Keluarga Sakinah. Watapone: Al-Risalah-Jurnal Hukum Keluarga Islam. Vol 1 no. 1 Juli 2014.Tamanni, Luqyan & Murniati Mukhlisin. 2013. Sakinah Finance Solusi Mudah Mengatur Keuangan Keluarga Islami. Solo: Tinta Medina.Wibawa, H. 2003. Perencanaan Keuangan Keluarga. Jakarta: Salemba Empat.Yin, Robert K. Tanpa Tahun. Studi Kasus Desain & Methode. Terjemahan oleh M. Djauzi Mudzakir. 2014. Jakarta: Rajawali Pers.